2022
DOI: 10.3389/fped.2021.793561
|View full text |Cite
|
Sign up to set email alerts
|

Transient Early Fine Motor Abnormalities in Infants Born to COVID-19 Mothers Are Associated With Placental Hypoxia and Ischemia

Abstract: Background: Long-term effects of Coronavirus Disease 2019 (COVID-19) on infants born to infected mothers are not clear. Fine motor skills are crucial for the development of infant emotional regulation, learning ability and social skills.Methods: Clinical information of 100 infants born to 98 mothers (COVID-19 n = 31, non-COVID-19 n = 67) were collected. Infants were follow-up up to 9 months post-partum. The placental tissues were examined for SARS-CoV-2 infection, pathological changes, cytokines, and mtDNA con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 54 publications
0
10
0
6
Order By: Relevance
“…These changes mainly include thrombosis, malperfusion and vasculopathy in both maternal and foetal circulations as summarized in Table 1 . Vascular changes may adversely affect the health of pregnant women and their unborn babies and cause severe health consequences [ 43 , 44 ].…”
Section: The Effect Of Covid-19 On Pregnanciesmentioning
confidence: 99%
See 2 more Smart Citations
“…These changes mainly include thrombosis, malperfusion and vasculopathy in both maternal and foetal circulations as summarized in Table 1 . Vascular changes may adversely affect the health of pregnant women and their unborn babies and cause severe health consequences [ 43 , 44 ].…”
Section: The Effect Of Covid-19 On Pregnanciesmentioning
confidence: 99%
“…Placental vascular changes due to COVID-19 infections during the third trimester have been extensively studied. Studies documented signs of maternal vascular malperfusion which included the presence of infarcts, thrombosis, increased syncytial knots, increased fibrin deposition, villous agglutination and accelerated villous maturation [ 44 , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [56] , [57] , [58] , [59] , [60] , [62] , [63] , [64] , [65] , 68 , 71 , 73 , 74 ]. Furthermore, subsequent studies that reported multi case investigations of placentae from COVID-19 positive mothers which presented different features of foetal vascular malperfusion including avascular villi, karyorrhexis, mural fibrin deposition, villous hypoplasia and chorangiosis [ 44 , 46 , 48 , 49 , 51 , 54 , 56 , 59 , 62 , 63 , 65 , 66 , 69 , 73 ].…”
Section: The Effect Of Covid-19 On Pregnanciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Respiratory chain subunit genes NADH:Ubiquinone oxidoreductase subunit A9 (NDUFA9), succinate dehydrogenase complex flavoprotein subunit A (SDHA) and cyctochrome C oxidase subunit 4I1 (COX4I1) were also decreased in symptomatic infected cases [ 30 ]. Mitochondrial DNA (mtDNA) was also decreased in infected placentae, potentially due to increased DNA oxidative damage [ 30 ], though another study found elevated mtDNA in infected placentae [ 29 ], indicating that further research is necessary to tease out the effect of SARS-CoV-2 infection on mtDNA levels. SARS-CoV-2 infection was also associated with aberrant mitochondrial reticulum and an increase in mitochondrial fission over fusion, accompanied by a decrease in genes involved in mitochondrial dynamics dynamin-1-like protein (DNM1L) and mitochondrial fission 1 protein (FIS1) [ 30 ] resulting in highly fragmented mitochondria [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…Namun, hubungan antara luaran perkembangan pada bayi dengan disfungsi mitokondria plasenta ibu yang terinfeksi covid-19 masih belum jelas. 13 Beberapa laporan kasus menemukan adanya MVM dan intervilositis histiositik kronis dengan nekrosis tropoblas pada plasenta ibu yang terinfeksi covid-19. 12,14,15,16 MVM plasenta ini dapat secara langsung mempengaruhi perkembangan janin dalam Rahim.…”
Section: Pendahuluanunclassified